2010
DOI: 10.1590/s0100-40422010000400028
|View full text |Cite
|
Sign up to set email alerts
|

Influência dos constituintes químicos dos extratos de diferentes matrizes na resposta cromatográfica de agrotóxicos

Abstract: Recebido em 9/9/09; aceito em 12/12/09; publicado na web em 26/3/10 INFLUENCE OF THE CHEMICAL CONSTITUENTS OF EXTRACTS FROM DIFFERENT MATRICES IN THE PESTICIDE CHROMATOGRAPHIC RESPONSE. Multiresidue methods for pesticides monitoring by GC are commonly employed, however, it is well known that the presence of compounds of the matrix introduces errors during the quantification. The main consequence of matrix effect is an increasing or decreasing analyte signal after the GC saturation with extracts of matrix. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…Analysing the loadings it is observed that the soil matrix was the only one that stood out from the rest. Similar results were found by Pinho et al (2010). It was also seen that the pineapple, tomato and grape matrices separated from the other matrices by the second component.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 86%
See 1 more Smart Citation
“…Analysing the loadings it is observed that the soil matrix was the only one that stood out from the rest. Similar results were found by Pinho et al (2010). It was also seen that the pineapple, tomato and grape matrices separated from the other matrices by the second component.…”
Section: Principal Component Analysis (Pca)supporting
confidence: 86%
“…This liquid was passed through 1.50 g of anhydrous sodium sulphate. The filtrate obtained (extract) was recovered in 10.0 mL volumetric flask with acetonitrile and the solution was stored in the freezer until the time of analysis by GC/ECD (Pinho, Silvério, Neves, Queiroz, & Starling, 2010).…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…59 Thus, in aqueous samples, the matrix effect can become more pronounced with increasing complexity. Thus, rainwater, groundwater and drinking water tend to have less matrix effect than estuarine waters and weir.…”
Section: Recovery and Matrix Effectmentioning
confidence: 99%
“…Components of this matrix showed high potential protective effects for analytes during analyses. 17 But despite these facts, few works in the literature have addressed the influence of tomato components for the pesticide adsorption in the chromatographic system. 18,19 Even after clean up stages of organic extracts of tomato (gel permeation chromatography, liquid-liquid extraction, matrix solid-phase dispersion etc.…”
Section: -9mentioning
confidence: 99%